Penyimpanan Sarana dan Prasarana Pendidikan - Siskawati, Garina; Hafiza, Dina; Choirunnisa, Essy Fitri; Purba, Yohana Damai Yanti; Setiyadi, Bradley; Saudagar, Ferdiaz (Universitas Batanghari Jambi, 2024)
The storage of educational facilities and infrastructure involves the action of storing school equipment in designated storage places. This research aims to understand the methods of storing these facilities. The research methodology employs a literature review by collecting and combining sources related to the storage of educational facilities and infrastructure. The research findings reveal various storage methods, including receiving, screening, and inspecting incoming goods. Subsequent steps involve examining items for storage, organizing them into specific groups, recording in acceptance books, issuing receipts, and warehouse notes. Plans are made for the storage location, ensuring quick retrieval when needed. Existing items must be received, registered, stored, sorted, maintained, and preserved in an orderly, fast, and secure manner. The research emphasizes managing the storage and use of all items in rooms and warehouses, periodic inventory control, reporting on the preservation conditions of items according to applicable regulations, and issuing items in accordance with the instructions for item issuance.